Speech acts in appeals for social distancing and public compliance intentions during the Covid-19 pandemic in Indonesia - Sultan Sultan; Muhammad Rapi; Hasnawi Haris; Muhammad Saleh (Universitas Pendidikan Indonesia, 2023)
Government-issued communication messages are critical in resolving health problems such as the COVID-19 pandemic. The decision of linguistic speech acts also influences the behavior of obedient and disciplined individuals. Gender, age, and race are all predictors of social distancing compliance (Pedersen Favero, 2020). However, no studies have been published examining the form of speech acts that can control public conduct in accordance with social distancing on each of these social variables. Thus, this study examined the intention of public compliance through the pragmatic interpretation of the government’s appeal for social distancing. The present study was conducted with a cross-sectional design survey involving 1339 respondents through online data collection. The findings of this study reveal that different speech acts have varying effects on people’s intentions to follow the health protocol appeal. This study makes a theoretical contribution by demonstrating that gender, age, and education level influence the perlocutionary style of speech actions in critical health communication. These findings will aid the government in developing effective messages on health risk reduction behavior through the selection of appropriate speech acts.